Pengaruh Kepemilikan Manajerial, Investment Opportunity Set (IOS), Ukuran Perusahaan Terhadap Nilai Perusahaan dengan Kebijakan Deviden sebagai Variabel Intervening (Sektor Manufaktur yang Terdaftar di Bursa Efek Indonesia 2015-2019) - Risal Rinofah; Ratih Kusumawardhani; Retno Dwi Pangesti (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of managerial ownership, IOS, firm size on firm value with policy intervention variables in the manufacturing sector listed on the Indonesia Stock Exchange 2015-2019. This research is quantitative with the type of secondary data. In this study using multiple linear regression analysis techniques, partial t test, and F statistical test. The results on the t test show that managerial ownership has no significant effect on dividend policy with a significant value of 0.898 > 0.05, IOS has a significant negative effect on policy dividends with a significant value of r 0.000 <0.05, firm size has a significant positive effect on dividend policy with a significant value of 0.006 <0.05. Managerial ownership has no significant effect on firm value 0.212 > 0.05, IOS has a significant effect on firm value with a significant value of 0.000 < 0.05, firm size has no significant effect on firm value 0.262 > 0.05, and policy dividends have no effect on firm value with a significant value of 0.972 > 0.05.